Risk factors for Alzheimer’s disease and cognitive function before middle age in a U.S. representative population-based studyResearch in context - Allison E. Aiello; Jennifer Momkus; Rebecca C. Stebbins; Yuan S. Zhang; Chantel L. Martin; Y. Claire Yang; Lauren Gaydosh; Taylor Hargrove; Adina Zeki Al Hazzouri; Kathleen Mullan Harris (The Lancet Regional Health. Americas)
Summary: Background: Alzheimer’s disease is a major health concern in the U.S., but most research has focused on older populations. We examined whether established risk factors and blood biomarkers are associated with cognition before midlife. Methods: Data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) were analyzed. Participants were enrolled in 1994–95 (grades 7–12) and followed through 2018. We cross-sectionally analyzed weighted survey and biomarker data from Waves IV and V. We measured the Cardiovascular Risk Factors, Aging, and Incidence of Dementia (CAIDE) score comprised of age, education, sex, systolic blood pressure, body mass index, cholesteroal, and physical activity and apolipoprotein E ε4 allele (APOE ε4) status. We also measured total Tau and Neurofilament light (NfL), high sensitivity C-reactive protein (hsCRP), Interleukin (IL)-1β, IL-6, IL-8, IL-10, and Tumor necrosis factor alpha (TNF-α). Outcomes included immediate word recall, delayed word recall, and backward digit span. Findings: Analytic sample sizes ranged from 4507 to 11,449 participants in Wave IV and from 529 to 1121 participants in Wave V. The survey-weighted median (IQR) age was 28 (26–29) years in Wave IV and 38 (36–29) years in Wave V. About half of the survey-weighted Wave IV participants were female (48.4–52.1% across analytic samples), 71.4–72.5% were White, 12.5–14.9% were Black, and 9.3–10.2% were Hispanic. In Wave V, 43.6–46.8% were female, 68.7–69.3% were White, 17.1%–20.0% were Black, and 7.3%–9.6% were Hispanic. The CAIDE score was associated with all cognition measures in Wave IV. For example, among adults aged 24–34, each 1-point increase in CAIDE was associated with a 0.03 standard deviation lower backward digit span score (95% CI: −0.04, −0.02). Total Tau was associated with immediate word recall in Wave V (β = −0.13, 95% CI: −0.23, −0.04). Wave IV hsCRP and IL-10 and Wave V IL-6, IL-1β, and IL-8 were also associated with lower cognitive scores. Interpretation: Key risk factors for Alzheimer’s Disease are linked to cognitive function as early as ages 24–44, highlighting the need for early prevention in the US. Funding: NIH P01HD31921, U01AG071448, U01AG071450, R01AG057800, P30AG066615, T32HD091058, P2CHD050924.